Site selection for new memorial park using GIS: muslim memorial park - Omar, Abdullah Hisam; Ismail, Norazman; Majeed, Zainal A. (2007)

(untitled)
The need for a cemetery (memorial park) is equally important like other needs of basic facilities. When developing a housing area, memorial park aspect has always been left out and has caused problems to the community because the local authority has no proper plan for a cemetery area. In due course, there is a requirement to find out a suitable new site for cemetery using GIS technology and digital mapping applications is. This method is expected to give solution to local authority when choosing an appropriate place for cemetery. Three main objectives drawn in this study will contribute effectively to the planning and selection of Muslim cemetery in Mukim Cheras area. Data collection of applicable spatial vector and raster as well as the attribute data from various agencies were made to achieve the research goal. The usage of Remote Sensing and GIS software such as Erdas Imagine 8.5 and ArcGIS 9.0 helps in facilitating this study. Various GIS analyses such as modeling analysis, buffering analysis and overlay analysis were carried out in order to ultimately produce a spatial product of suitable criterion. The end products portraying suitable areas for cemetery with spatial location, within related cadastral lot and slope condition suitability can contribute values and standards to the urban planning unit of Local Authority. The method and analysis carried out and the final product achieved by means of GIS application can allegedly assist Local Authority in efficiently planning few other developments in line with the neighborhood needs. The GIS method utilized in this study will facilitate urban planning authority in identifying areas for various developments and thus minimizing the issues that relates to the lack of land for cemetery in our country. Furthermore, planning developments can be more effectively enhanced through processing and visualization of relatively accurate physical location of areas in analysis in a computing environment.